Legislative Challenges and Their Impact on the Effectiveness of Small Enterprises in Achieving Sustainable Development - Mahdi Khalaf, Lect .Dr. Nada (Basra studies journal, 2025)
Legislation plays a fundamental role in financing small enterprises by providing a regulated and supportive legal framework for small and medium-sized enterprises (SMEs). By enacting laws that organize and protect small businesses, legislation naturally encourages innovation and expansion. It also facilitates access to financing and provides the necessary support for small enterprises. Undoubtedly, the banking sector is one of the most vital sectors in any country, as it plays a significant role in economic activity by supplying the liquidity required to fund these enterprises. Moreover, banks are influential institutions in both fiscal and monetary policy, particularly in the areas of domestic and foreign credit, given their intermediary role between lenders and investors. This, in turn, strengthens the national economy and promotes social welfare by reducing poverty and eliminating unemployment, thereby contributing to the achievement of sustainable development.